PERANCANGAN SECURITY SISTEM JARINGAN BERBASIS UNTANGLE FIREWALL PADA UNISADHUGUNA INTERNATIONAL EDUCATION - Mauludin, Haris; Kuswanto, Herman (Jurusan Informatika Universitas Tanjungpura, 2021)
AbstracÂ In a computer network system, it is definitely not free from a problem that often occurs, as well as in Unisadhuguna where several problems have occurred in the computer network system either from the system or from the user. The problem that occurs to the user is that the full access to the internet network that is obtained is often used for several things that are outside the work limit, often used to access a website that can make work neglected even to access a website that smells of ponography, other problems are less the effectiveness of the running computer network system. To overcome the above problems, a study was carried out to improve the computer network system that was running above, it was proposed to use a computer network security based on the Untangle application and change the computer network scheme that was running on Unisadhuguna. By using the network security method, the results obtained later by each computer is internet access which is regulated by the Untangle application, and the result is that the computer network security system will filter and block an application that is often used by users who are not related to work.Â Keywords: Computer Network, Untangle Application, client